2022
DOI: 10.1001/jamanetworkopen.2022.24621
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between State-Level Severe Maternal Morbidity and Other Perinatal Indicators

Abstract: This cross-sectional study examines state-level associations between severe maternal morbidity and other perinatal indicators, including prepregnancy hypertension, prepregnancy diabetes, prepregnancy obesity, low-risk cesarean delivery, preterm birth, and maternal and infant mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 6 publications
1
6
0
Order By: Relevance
“…Our studies of HCUP-SID data published in JAMA Network Open 5,6 also found large state-level variation in SMM at delivery but with little geographic patterning, and state rates were not associated with most other perinatal indicators, including maternal mortality. Several states experienced rapid increases in SMM, and the correlation between state-level SMM rates in 2012 and 2019 was only 0.47.…”
supporting
confidence: 55%
See 1 more Smart Citation
“…Our studies of HCUP-SID data published in JAMA Network Open 5,6 also found large state-level variation in SMM at delivery but with little geographic patterning, and state rates were not associated with most other perinatal indicators, including maternal mortality. Several states experienced rapid increases in SMM, and the correlation between state-level SMM rates in 2012 and 2019 was only 0.47.…”
supporting
confidence: 55%
“…Examination of Transformed Medicaid Statistical Information System Analytic Files complements existing population-based, all-payer data from the Healthcare Cost and Utilization Project State Inpatient Databases (HCUP-SID) accessible through HCUP Fast Stats 3 (by state of hospitalization) and the Title V Information System 4 (by state of residence), which use updated SMM codes to better bridge the International Classification of Diseases, Tenth Revision, Clinical Modification-Procedure Coding System transition. 5 Our studies of HCUP-SID data published in JAMA Network Open 5,6 also found large state-level variation in SMM at delivery but with little geographic patterning, and state rates were not associated with most other perinatal indicators, including maternal mortality. Several states experienced rapid increases in SMM, and the correlation between state-level SMM rates in 2012 and 2019 was only 0.47.…”
mentioning
confidence: 76%
“…We used International Classification of Diseases, Clinical Modification (ICD-CM) diagnosis and procedure codes to identify if any of the 20 indicators of SMM occurred during the delivery hospitalization. As is now recommended by the US Health Resources and Services Administration and others, we did not include blood products transfusion as an indicator of SMM . The SMM indicators represent either serious complications of pregnancy or delivery, such as sepsis or acute kidney failure, or procedures used to manage serious conditions, such as mechanical ventilation or hysterectomy.…”
Section: Methodsmentioning
confidence: 99%
“…There is a positive volume-outcome association for many surgical conditions, such as trauma care and complex surgical procedures, and for neonatal intensive care units, but there are less available data for obstetric services. Some evidence indicates that the volume of births is associated with maternal outcomes, with lower-volume facilities having higher risks of mortality and serious morbidity, although this evidence is not consistent for all maternal outcomes or across all types of rural/urban geographic locations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation